Scotch Pine Regeneration in Magnesite Pollution Conditions in South Ural, Russia - Mohnachev, Pavel; Menshikov, Sergey; Makhniova, Svetlana; Zavyalov, Konstantin; Kuzmina, Nadezda; Potapenko, Anton; Ayan, Sezgin; Laaribya, Said (Hrvatski Sumarski Institut (Croatian Forest Research), 2018)
Background and Purpose: Technogenic load is considered to be one of the major factors which destabilize forest ecosystems. The impact of chronic aero technogenic pollution near large industrial centers severely affects the plants in these areas; thus, plants cannot fulfill their aesthetic and air-cleaning role. Therefore, many studies have been carried out on technogenic pollution and particularly on magnesite pollution. The aim of the study is to investigate characteristics of the Scotch pine natural regeneration process under the forest canopy in magnesite pollution conditions. Materials and Methods: The research was carried in an aero-technogenic emission zone of Kombinat Magnezit, in South Ural, Russia. The purpose is to assess the soil suitability for reforestation in various degrees (PS-2: High pollution zone, PS-5: Average pollution zone, PS-3: Low pollution zone, PS-4: Very weak pollution zone, and PS-K: Control area) of magnesite pollution. Experimental Plots (PS) are in similar conditions regarding forest vegetation. The major factors that can influence the natural regeneration, such as the quantity of seeds produced by the parents trees, stand density (the number of trees per 1 ha), the composition of the upper horizon of the soil and height, its density, live ground cover (LGC) phytomass and pH of the upper root-inhabited soil layer have been measured. Results: The results of this study showed that in PS-K conditions a large number of seeds, thin forest litter, small phytomass of alive ground cover, and slightly acidic pH of the root zone of the soil can be found. The dense forest laying, generally composed of fresh and weakly decomposed layers, inhibits seed germination from reaching the mineral soil layer, which results in mortality. Conclusions: It was evaluated that the success of natural regeneration is effected by the stand density and the occurrence of undergrowth of Scots pine. Soil remediation can positively affect the natural rejuvenation process. Moreover, seed supplementation can play a major role in successful natural rejuvenation.
Keywords: soil toxicity; natural regeneration; magnesite pollution; aero-technogenic; Forestry; seeds; SD1-669.5; weed; 15. Life on land; 13. Climate action